Epidemiological characteristics and influencing factors of tuberculosis aggregation in schools in Wuhan, China during 2017–2022 - Zhang, Zhengbin; Wu, Gang; Yu, Aiping; Hu, Jing; Zhang, Wei; Lu, Zhouqin; Wu, Jun; Wang, Lina; Wang, Xiaojun; Wang, Jianjie; Wang, Guiyang; Li, Yuehua; et al. (Frontiers in Public Health, 2024)
Wuhan is located in the hinterland of China and east of Hubei Province, at the intersection of the Yangtze River and Hanshui River. It is an important industrial base, a scientific and educational base and a comprehensive transportation hub. There are nearly a thousand schools of all kinds , with about 2.2 million students in them, among which college or university students account for about 60% , and the geographical location of colleges is relatively concentrated, which is prone to tuberculosis clustering epidemic.This study was undertaken to analyze the epidemiological characteristics and influencing factors of tuberculosis aggregation in schools, so as to provide the basis for scientific development of tuberculosis prevention and control strategies and measures in schools.This study analyzed the epidemic characteristics of tuberculosis aggregation in schools in Wuhan in 2017 - 2022, collecting the relevant data of tuberculosis prevention and control in all kinds of schools by using questionnaire star,and analyzing the influencing factors of tuberculosis aggregation by using multi factor Logistic regression analysis.54 outbreaks in schools were reported , which involved 37 schools, including 32 colleges or universities and 5 senior schools, 176 cases were reported, among which 73 cases were positive for pathogens and 18 cases of Rifampicin or Isoniazide resistant, the median duration of single cluster epidemic was 46 (26,368) days, universities are more prone to cluster outbreaks than middle schools (χ 2 ＝105.160, P＝0.001),The incidence rate of male was higher than that of female ( χ 2 ＝ 12.970, P＝0.001). The results of multivariate logistic regression analysis showed Boarding school (OR=7.60) is the risk factors for tuberculosis cluster epidemic in schools. and the small number of students(OR=0.50), schools in city (OR=0.60) , carry out physical examination for freshmen (OR=0.44) , carry out illness absence and cause tracking (OR=0.05), dormitories and classrooms were often ventilated(OR=0.16) ,strictly implement the management of patients' suspension from school (OR=0.36),timely seeking medical consultation (OR=0.32)are the protective factors .We successfully identified that epidemiological characteristics and influencing factors of tuberculosis aggregation in schools , and point out the direction for schools to improve TB prevention and control measures in their daily lives.